2022
DOI: 10.1155/2022/8178782
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Identification of a Ferroptosis‐Related Prognostic Signature in Sepsis via Bioinformatics Analyses and Experiment Validation

Abstract: Ferroptosis is a new type of programmed cell death that is different from apoptosis, cell necrosis, and autophagy, which might be involved in development of sepsis. However, the potential role of ferroptosis-related genes (FRGs) in sepsis remained unclear. We identified 41 ferroptosis-related differential expression genes by weighted correlation network and differential expression analysis. The hub module of 41 ferroptosis-related differential expression genes in the protein-protein interaction network was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Li et al [ 30 ] found that HIF-1 in myeloid cells α deletion can significantly reduce TNF- α expression of succinic acid and glutamine, as important intermediates of glucose metabolism, and can improve glucose metabolism in sepsis. Studies have shown that succinic acid and glutamine can directly or indirectly increase HIF-1 α level and stability and promote the production of inflammatory cytokines [ 31 ]. So far, the research on the effect of ferroptosis on succinic acid is not clear.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…Li et al [ 30 ] found that HIF-1 in myeloid cells α deletion can significantly reduce TNF- α expression of succinic acid and glutamine, as important intermediates of glucose metabolism, and can improve glucose metabolism in sepsis. Studies have shown that succinic acid and glutamine can directly or indirectly increase HIF-1 α level and stability and promote the production of inflammatory cytokines [ 31 ]. So far, the research on the effect of ferroptosis on succinic acid is not clear.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…Based on the positive regulation of autophagy by WIPI1, quantifying the expression of WIPI1 mRNA or the number of WIPI1 puncta is considered a reliable method to assess the level of autophagosome formation ( Proikas-Cezanne et al, 2007 ; Tsuyuki et al, 2014 ). Consistent with our findings, in another bioinformatics study on ferroptosis-related genes, WIPI1 was found to be elevated in sepsis patients and correlated with patient outcomes ( Zhu et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…This prognostic signature demonstrated good predictive performance for 28-day mortality in the internal and external validation datasets [ 27 ]. Zhu et al [ 36 ] identified a ferroptosis-related prognostic signature ( TLR4 , WIPI1 , and GABARAPL2 ), and Jiang et al [ 37 ] developed a signature consisting of nine inflammatory response-related genes ( CCL22 , CX3CL1 , CXCR6 , FFAR2 , FPR1 , HBEGF , ITGA5 , RGS16 , and SELL ) to predict prognosis. The AUC of the HLMRG signature was comparable to the AUCs of the signatures identified by the groups aforementioned, except that it was significantly higher than that of the signature identified by Zhu and his colleagues (0.674 vs. 0.599, P = 0.002; Fig.…”
Section: Discussionmentioning
confidence: 99%